Current-Mode MOS Only Precision Full-Wave Rectifier. Issue 1 (2nd January 2023) - Kumar, Atul; Chaturvedi, Bhartendu
Abstract : The paper deals with the realization of a current-mode precision full-wave rectifier using one extra-X second generation current conveyor and two metal-oxide-semiconductor (MOS) switches. The structure of the circuit is simple as it is implemented using fewer MOS transistors and does not use any external resistor. The linearity range of the presented rectifier is good i.e. ±300 µA and its higher operating frequency is 30 MHz which is also quite good. Moreover, the circuit performance is less affected by temperature variations. Additionally, the proposed rectifier circuit is suited to low-voltage and low-power applications as it dissipates only 0.2 mW power at ±0.9 V power supplies. The theoretical presumptions are validated through simulation results which are performed via HSPICE using the 0.13 µm IBM technology. Furthermore, experimental results are also included to validate the practicality of the circuit.